PENGEMBANGAN GAME EDUKASI PAKAIAN TRADISIONAL INDONESIA BERBASIS ANDROID - Arifin, Ardian; Marlianto, Ferry; Budiman, Aris (Information Technology and Science (ITScience), 2019)
Culture in Indonesia has a lot of diversity. Indonesia which has many provinces also has many cultures. One of the cultures that exist in Indonesia is raditional clothing. Traditional clothing, a characteristic of adat and culture in each region and also used in each traditional ceremony. Along with the development of the times, the concern for the preservation of national culture, especially traditional clothing, was very minimal. For example, the lack of recognition and socialization of Indonesian culture in the community is one of the important factors why people's interest is lacking in traditonal clothing. This study aims to develop the development of an Android-based educational game on traditional Indonesian clothing. The method used in this study uses Research and Development methods. The results of this study were developed an educational game